2020
DOI: 10.2174/1871520620666200331102609
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Effect of Orange Peel and Selenium against 17β-Estradiol- Induced Chronic Non-Bacterial Prostatitis in Rats

Abstract: Background: Prostate Cancer (PCa) is defined as a major health problem facing the male population. Aims: We aimed to investigate the protective effects of Orange Peel Extract (OPE) and/or selenium (Se) on chronic non-bacterial prostatitis in a rat model. Methods: Fifty-six adult male Wistar albino rats were castrated; after 5 days, they were divided randomly into eight groups (n= 7). The control group received saline treatment; while 17β-estradiol (E2) (0.25mg/kg) was injected subcutaneously in rats from Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…[ 31,32 ] Moreover, the selected doses of selenium have been established in the literature to effectively protected against oxidative damage, prostatitis, and neurotoxicity induced by various toxicants in rats. [ 33‐35 ] The animals were weighed 24 h after the final treatment while the blood collected from the animals was processed to get the serum which was subsequently used for hormonal assays. The animals were sacrificed using light ether anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…[ 31,32 ] Moreover, the selected doses of selenium have been established in the literature to effectively protected against oxidative damage, prostatitis, and neurotoxicity induced by various toxicants in rats. [ 33‐35 ] The animals were weighed 24 h after the final treatment while the blood collected from the animals was processed to get the serum which was subsequently used for hormonal assays. The animals were sacrificed using light ether anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Nonbacterial prostatitis was induced in an animal model after 5 days of oestradiol administration accompanied with significantly increased IL2 and PCA3 mRNA expression levels. To this end, utilising anti-inflammatory effects of the orange peel extract, containing selenium, the inflammatory process has been suppressed accompanied by decreased levels of the above parameters measured [79]. The Prostate Cancer Study throughout Life (PROCA-life) investigating potential relationship between high sensitive CRP (hs-CRP) levels and white blood cell count (WBC) demonstrated that a significant increase in hs-CPR levels was associated with high PCa risks.…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…6 Notably, inflammation plays a key role in the pathogenesis of many diseases. [7][8][9][10] Antibiotics, botanicals, alpha-blockers, and non-steroidal anti-inflammatory analgesics are common treatment methods for CNP. 11 However, chemicals are not appropriate as permanent therapeutics because they are prone to adverse reactions.…”
Section: Introductionmentioning
confidence: 99%